Effects of some factors on extraction of celery CEL I nuclease - CUI Hai-rui; LI Chun-nan; SUN Jie; CUI Bi-jun (浙江大学学报. 农业与生命科学版, 2011)
In order to extract celery CEL I nuclease effectively and use it to develop the detection method for point mutations, the effects of varieties, organs, developmental stages and pH of extraction buffer on its extraction amounts were analyzed and its enzymatic activity for mismatch cleavage was also characterized by using DNA heteroduplexes containing a single mismatch as substrates. Results showed that differences of CEL I amounts extracted among varieties and organs were significant at 5% and 1% level, respectively. The cultivar Thailand Huangxinqin showed the highest extractive amount among three different varieties (Xuebai, Wentula and Thailand Huangxinqin) compared, while the leaf showed much higher extraction amounts than the stalk and root among three different organs tested. The effect of developmental stages on the CEL I extraction was compared by using the variety Shanghai Huangxinqin as extractive material and it was higher at reproductive stage than that at vegetative stage. The pH of extraction buffer also showed important effect on the CEL I extraction, and the higher extraction amount was obtained by using the extraction buffer with pH 7.5 than that with pH 5.5 and pH 9.5. Tests on enzymatic activity showed that the mismatch in DNA heteroduplexes could be effectively recognized and cleaved by the CEL I crude extracts.